2003
DOI: 10.1007/s10071-003-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural innovation and transmission of tool use in wild chimpanzees: evidence from field experiments

Abstract: Chimpanzees (Pan troglodytes) are the most proficient and versatile users of tools in the wild. How such skills become integrated into the behavioural repertoire of wild chimpanzee communities is investigated here by drawing together evidence from three complementary approaches in a group of oil-palm nut- ( Elaeis guineensis) cracking chimpanzees at Bossou, Guinea. First, extensive surveys of communities adjacent to Bossou have shown that population-specific details of tool use, such as the selection of specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
346
3
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 430 publications
(388 citation statements)
references
References 31 publications
26
346
3
3
Order By: Relevance
“…B 370: 20140348 remained difficult to ascertain due to the time consuming challenge of habituating several wild chimpanzee communities. Only a few immigration events have been observed in the past, which have added valuable information to understanding the transmission of social knowledge between chimpanzee communities [44,48,49,52]. Previous studies conducted in three neighbouring chimpanzee communities in the Taï National Park demonstrated that cultural traits were maintained in neighbouring groups despite regular individual transfer [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B 370: 20140348 remained difficult to ascertain due to the time consuming challenge of habituating several wild chimpanzee communities. Only a few immigration events have been observed in the past, which have added valuable information to understanding the transmission of social knowledge between chimpanzee communities [44,48,49,52]. Previous studies conducted in three neighbouring chimpanzee communities in the Taï National Park demonstrated that cultural traits were maintained in neighbouring groups despite regular individual transfer [42].…”
Section: Discussionmentioning
confidence: 99%
“…This could be a reason why innovations and also behaviour of immigrants does not seem to spread throughout the group. Only if innovators persist can they add to the behavioural pool by disseminating their innovations once they are older [48,76]. However, the ontogeny of cultural traits within a community remains a topic of investigation as only a few studies have reported the spread of new behaviours within a chimpanzee community [13,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsuzawa and colleagues (8,10,25,26) have pioneered an ''outdoor laboratory'' to document the transmission of nut-cracking behavior in the wild, but the logistics of such studies have limited the application of control conditions possible in captive experiments, in which some chimpanzees see no model, allowing a more conclusive establishment of the role of social learning.…”
mentioning
confidence: 99%
“…Cerca 17% dos episódios foram observados por coespecíficos. Como em chimpanzés (Biro et al, 2003), os indivíduos observadores foram na maioria, mais jovens que os alvos.…”
Section: Observação E Aprendizagem Socialmente Mediada Na Quebra De Funclassified